Chronic Wounds, Biofilms and Use of Medicinal Larvae. (14th February 2013) - Cowan, Linda J.; Stechmiller, Joyce K.; Phillips, Priscilla; Yang, Qingping; Schultz, Gregory
Abstract : Chronic wounds are a significant health problem in the United States, with annual associated costs exceeding $20 billion annually. Traditional wound care consists of surgical debridement, manual irrigation, moisture retentive dressings, and topical and/or systemic antimicrobial therapy. However, despite progress in the science of wound healing, the prevalence and incidence of chronic wounds and their complications are escalating. The presence & complexity of bacterial biofilms in chronic wounds has recently been recognized as a key aspect of non-healing wounds. Bacterial biofilms are sessile colonies of polymicrobial organisms (bacteria, fungus, etc.) enclosed within a self-produced exopolymeric matrix that provides high levels of tolerance to host defenses, antibiotics and antiseptics. Thus, there is a need for alternative therapies to reduce biofilms in chronic wounds. In this report, we present initial findings from in vitro experiments which show that larval debridement therapy with disinfected blow fly larvae ( Phaenicia sericata ) reduced total CFUs (6-logs) of planktonic and mature biofilms of Pseudomonas aeruginosa or Staphylococcus aureus grown on dermal pig skin explants by 5-logs after 24 hours of exposure, and eliminated biofilms (no measurable CFUs) after 48 hours of exposure.